The Political Economy of Sustainable Development in Indonesia - Wibowo, Dradjad H.; Rakatama, Ari; Irhamna, Ariyo D.P. (Sustainability Science and Resources, 2021)
Political economy concerns with how actual policies deviate from economic optimality. This study evaluates Indonesia’s progresses toward sustainable development goals (SDGs) from the political economy viewpoint. The authors discuss Indonesia’s Voluntary National Reviews (VNRs) and critically analyse its COVID-19 pandemic control policy given the policy’s importance to SDG 3 (good health and well-being) and SDG 8 (decent work and economic growth). Indonesia chooses to opt-out strict public health restrictions because of the government’s preoccupation with economic growth, the large number of workers relying on daily income and its state of democratic consolidation. This results in Indonesia’s failure to control the pandemic and to avert economic recession. Indonesia correctly anticipates global vaccine nationalism and secures adequate vaccine supplies primarily from China. Vaccination becomes Indonesia’s key pandemic strategy. This study shows how indispensable partnerships (SDG 17) are for achieving SDGs, presenting the case of the Indonesian Forestry Certification Cooperation’s work in forest certification and sustainable forest management.